PRIVACY WITH PUBLIC ACCESS: DIGITAL MEMORIALS ON QR CODES - Gotved, Stine; Bjerager, Klaus (AoIR Selected Papers of Internet Research, 2014)
The focus in this short paper is how digital memorials perforate the (already uneasy) distinction between private and public, both in emotional and physical space. As a contemporary parallel to Meyrowitz’ (1985) elaboration of Goffman’s (1958) front- and backstage1, digital memorials are making the private grief visible to a much larger public than before. This goes for the many variations of memorials found in social media and throughout the web (Gotved, 2014), whatever the set-ups for accessibility might be. Indeed, the fast growing research area on digital memorials draws on the very fact of public (or semi-public) access, combined with different takes on participation and ethical issues.